Breed-Specific Magnetic Resonance Imaging Characteristics of Necrotizing Encephalitis in Dogs - Flegel, Thomas (Frontiers in Veterinary Science, 2017)
Diagnosing necrotizing encephalitis, with its subcategories of Necrotizing Leukoencephalitis and Necrotizing Meningoencephalitis, based on MRI alone can be challenging. However, there are breed specific imaging characteristics in both subcategories that allow establishing a clinical diagnosis with a relatively high degree of certainty. Typical breed specific imaging features, such as lesion distribution, signal intensity, contrast enhancement and gross changes of brain structure (midline shift, ventriculomegaly, brain herniation) are summarized here, using current literature, for the most commonly affected canine breeds: Yorkshire Terrier, French Bulldog, Pug and Chihuahua.